The Relationship Between Classroom Management and Learning Motivation with Student Learning Outcomes in Junior High Schools - Hendro S. Lumunon; Jeffry Sony Junus Lengkong; Viktory N. J. Rotty; Romi J. Mongdong (JR Education, 2026)
This study aims to analyze the relationship between classroom management and learning motivation, both partially and simultaneously, on student learning outcomes at SMP Negeri 1 Modoinding, South Minahasa Regency. The research method used is a quantitative correlational approach. The population in this study was all 91 ninth-grade students at SMP Negeri 1 Modoinding. Considering the limited population, this study used the Total Sampling technique, where all members of the population were used as research respondents. Data collection instruments were in the form of questionnaires for the variables of Class Management (X1) and Learning Motivation (X2), as well as report card documentation for the Learning Outcome variable (Y). The data were analyzed using correlation and multiple linear regression techniques. The results of the study showed that: (1) there is a positive and significant relationship between Class Management and Learning Outcomes; (1) there is a positive and significant relationship between Learning Motivation and Learning Outcomes; and (3) simultaneously, Class Management and Learning Motivation are significantly related to student Learning Outcomes at SMP Negeri 1 Modoinding. These findings indicate that optimizing student learning outcomes is highly dependent on teachers' ability to create a conducive classroom climate and their ability to spark students' intrinsic and extrinsic motivation. The implications of this research emphasize the importance of developing teacher managerial competencies in rural schools to ensure that the quality of learning outcomes is comparable to those in urban areas.